Disabled student advocacy to enhance accessibility and disability inclusion in one School of Social Work. (11th August 2021) - de Bie, Alise; Kumbhare, Shaila; Mantini, Sarah; Evans, Jessica
Abstract : In this article, current and former social work students with disabilities consider how the student Disability Action Group has facilitated greater accessibility and disability inclusion in our Canadian university's School of Social Work. After reviewing the relative absence of disabled student voices in the published literature on disability/accessibility advocacy initiatives in Canadian social work education, we reflect on the work of the Disability Action Group and the successes and challenges we have faced. We encourage other disabled social work students to collectively advocate for their learning needs and call on faculty and staff to better support us in enhancing accessibility and documenting and sharing student efforts to do so.